2016
DOI: 10.1155/2016/7650530
|View full text |Cite
|
Sign up to set email alerts
|

Normal Non-HDL Cholesterol, Low Total Cholesterol, and HDL Cholesterol Levels in Sickle Cell Disease Patients in the Steady State: A Case-Control Study of Tema Metropolis

Abstract: Background. Abnormal lipid homeostasis in sickle cell disease (SCD) is characterized by defects in plasma and erythrocyte lipids and may increase the risk of cardiovascular disease. This study assessed the lipid profile and non-HDL cholesterol level of SCD patients. Methods. A hospital-based cross-sectional study was conducted in 50 SCD patients, in the steady state, aged 8–28 years, attending the SCD clinic, and 50 healthy volunteers between the ages of 8–38 years. Serum lipids were determined by enzymatic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…Moreover, if SCC lipids profile presents intermediate values between GGP and SCA, the distinction between SCA and SCC lipid profiles is partially due to higher TG levels in SCA, with unexpected similar values of SCA apoB levels than in SCC. This observation is consistent with the presence of high levels of very low density lipoproteins in SCA [ 16 , 28 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, if SCC lipids profile presents intermediate values between GGP and SCA, the distinction between SCA and SCC lipid profiles is partially due to higher TG levels in SCA, with unexpected similar values of SCA apoB levels than in SCC. This observation is consistent with the presence of high levels of very low density lipoproteins in SCA [ 16 , 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to SCA, the plasma lipid profile of SCC patients has been poorly described up to now [ 7 , 10 , 16 ]. This study clearly revealed two very different SCC and SCA lipid profiles, both of them being distinct from their GGP’s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-HDL-C is a cholesterol carried by apolipoprotein B, including those carried by LDL-C and VLDL-C, and is considered a useful marker of atherosclerosis [ 48 ]. Previous studies performed in individuals with cardiovascular disease reported high non-HDL-C levels [ 49 , 50 ]; however, no significant alterations in non-HDL-C levels were found in SCD individuals [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…TC/HDL-C, LDL-C/HDL-C, and triglyceride/HDL-C ratios were calculated to evaluate cardiovascular risk [ 27 31 ]. In addition, non-HDL-C was calculated by TC–HDL-C [ 32 ].…”
Section: Methodsmentioning
confidence: 99%